Long-Term Trends in Marriage Timing and the Impact of Migration, the Netherlands (1650-1899) - Charlotte Störmer; Corry Gellatly; Anita Boele; Tine De Moor (Historical Life Course Studies)
The features of historical marriage patterns have been linked to debates in social and economic history about economic growth and female agency. However, there is a lack of empirical evidence on the demographics of marriage prior to the nineteenth century. Here, we study trends in sex-specific ages at first marriage, regional variation and the impact of migration on marital timing in the Netherlands in the period 1650-1900. We make use of two new large historical datasets, namely an aggregation of Dutch genealogies and the transcribed marriage banns of Amsterdam. This allows us to understand the features and developments of marriage ages from a long-term perspective in what is known as one of the core-areas of the so-called European Marriage Pattern. Our results show high marriage ages for both sexes from the beginning of our study period, increasing until the mid-19th century. A closer look at regional variation reveals clear differences between the provinces and between urban and rural settings with those in the western part of the country and in urban centers marrying earlier. Migrating individuals married on average later than non-migrating individuals both compared to men and women in the receiving community, as to the ‘stayers’ in the location of origin. As later marriage implies a reduction of the window of fertility, especially for women, our results suggest that migration and increasing regional mobility might have been an important driver of the demographic shift toward higher marriage ages and lower fertility in Europe between the 17th and 19th centuries.